AKTIVITAS ENZIM KATEPSIN PADA IKAN LELE (Clarias sp.) PADA PERLAKUAN SUHU DAN SUBSTRAT YANG BERBEDA - Anhar Rozi; Ikhsanul Khairi; Reni Tri Cahyani; Stephani Bija; Nurhikma Nurhikma; Nuring Wulansari; Deden Yusman Maulid; Siluh Putu Sri Dia Utari; Diah Anggraini Wulandari; Tati Nurhayati (Universitas Teuku Umar, 2020)
Cathepsin was proteolytic enzyme which is found animal tissues included fish. Cathepsin found in fish muscle tissue, cathepsin and other hydrolyzing enzymes were place in subcellular organelles and divided into two places, that was in muscle fibers and extracellular matrix. The aimed of this study was to the characterization of cathepsin enzyme especially catfish. So that in enviromental condition that can increased the activity of cathepsin enzyme an approtiate handling process can be carried out. The method of analyze enzyme activity, while the measurement of protein concentration refered to Bradford (1976). The treatments in this study was determination temperature (30oC, 40oC, 50oC, dan 60oC) and substrate (1.5% 2%, 2.5%). The result showed of enzyme activity with detrmination temperature very influential and fluctuating, the optimum temperature was 30oC where the activity reaches 0.38 U/ml. The best activity treatment of substrate was 1.5% where the activity reaches 0.42 U/ml. BSA Standard curve with regression equation y = 0.95x + 0.109.Keywords: Cathepsin, enzyme, substrate, temperature